2021
DOI: 10.15537/smj.2021.42.9.20210126
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Practice Guidelines for Liver Transplantation in Saudi Arabia

Abstract: The first human liver transplantation (LT) in the Kingdom of Saudi Arabia (KSA) was performed in 1990, but the first LT program was commenced in 1994. 1 Until 1997, all LTs in KSA were from deceased donors. 1,2 The living donor LT (LDLT) program for children started in 1997, and the LDLT program for adults was initiated in 2001. 3 Thus, as of 2017, there were 2,233 LTs conducted: 1,133 livers from livingrelated donors, 95 from living-unrelated donors, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 328 publications
(599 reference statements)
0
4
0
Order By: Relevance
“…Within the Kingdom of Saudi Arabia (KSA), four centers offer LTs, and all four centers perform LDLTs, while only three perform DDLTs [37]. Each center that performs LTs has its own LT waiting list, with no national organ transplantation list [38].…”
Section: Kingdom Of Saudi Arabiamentioning
confidence: 99%
See 1 more Smart Citation
“…Within the Kingdom of Saudi Arabia (KSA), four centers offer LTs, and all four centers perform LDLTs, while only three perform DDLTs [37]. Each center that performs LTs has its own LT waiting list, with no national organ transplantation list [38].…”
Section: Kingdom Of Saudi Arabiamentioning
confidence: 99%
“…The Saudi Center for Organ Transplantation oversees and manages the donation process while collaborating with individual centers [39]. Although HCV is the most common indication for LT, the proportion of patients with MASH is increasing [37].…”
Section: Kingdom Of Saudi Arabiamentioning
confidence: 99%
“…Fever is not always present due to the degree of immunosuppression. Therefore, clinical history and a complete physical examination, in addition to complementary exams, are essential in the evaluation of the transplant patient with any symptom without an apparent cause, as it may be because of an infectious condition (Abaalkhail et al, 2021).…”
Section: Monitoring Msud After Ltmentioning
confidence: 99%
“…Thus, a personalized therapy for HCC recurrence post-LT was recommended with no evidence supporting the use of sorafenib in patients with disseminated HCC recurrence. 77 The differences in outcomes among HCC patients who received sorafenib are often associated with their underlying hepatitis virus etiology at presentation. 46,[78][79][80] Our survey results showed that sorafenib was prescribed to only a quarter of patients ineligible for atezolizumab plus bevacizumab (Figure 5C).…”
mentioning
confidence: 99%